PARTICIPATORY APPROACH IN TO EMPOWER COMMUNITY DEVELOPMENT - Ageng Widodo; Vici Prihmaningrum AM; Ahmed Abdul Malik (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
Community participation is one of the most critical aspects of community development and empowerment. The high or low level of community participation is seen by the community's desire and the people's support to bear costs or labor in implementing government development projects. This study aims to describe and analyze the concept of andragogy and participatory implementation, especially in the community development process. The study employed a qualitative approach with a literature review data collection technique. The results showed that the stages in community participation cover decision-making, planning, implementation, and the evaluation or monitoring of activities. In addition, the forms of community participation are tangible (natural) and abstract (not actual). The constraints of community participation can be seen from internal and external factors.